Evaluation of effective diffusivity correlations for soybeans in thin layer drying - Felipe d'Avila; Rafael Maurício Urnau; Amanda Mansano Zanella Blauth; Marcos Flávio Pinto Moreira (The Journal of Engineering and Exact Sciences)
Soybean is one of the main crops in the world and drying plays an important role in maintaining the quality of the grains. The present study aimed to evaluate different existing models regarding the ability to predict the effective diffusivity of soybeans, an important parameter in studies of the operation. The slope method was used to determine the effective diffusivity, starting from the second Fick's Law, with negligible shrinkage and external mass transfer resistance. The parameter was analyzed as being dependent on both temperature and moisture content. The correlation proposed by Dotto et al. (2018) was the one with the lowest average error (0.048%) for the consideration of an average effective diffusivity. In order to consider a punctual effective diffusivity, modifications were made to the Dotto model, providing a maximum error of 2.6%.